Formulation development and evaluation of zolmitriptan oral soluble films using 22 factorial designs - Koteswari, Poluri; Sravanthi, G. Puja; Mounika, M.; Rafi, S. K. Mohammed; Nirosha, K. (International Journal of Pharmaceutical Investigation)
Objective: The present investigation involves the development of zolmitriptan oral soluble film (OSF) formulations and optimization with quality by design (QBD) using natural polymers and evaluation. Materials and Methods: Initially, various natural polymers such as sodium alginate, pectin, and gelatin were screened by casting films using solvent casting technique and the prepared films were evaluated. Based on the physical and mechanical properties, sodium alginate was selected as best film former and zolmitriptan‑loaded films were casted. The formulation was optimized with the help of 22 factorial experimental designs (QBD) in which sodium alginate concentration and plasticizer concentrations were used as factors and at two levels. The drug‑loaded films were evaluated for various mechanical, physicochemical properties, and in vitro drug release properties. Factor effects were interpreted by calculating the main factor effects and by plotting the interaction plots. Results: Thickness of the films, disintegration time, and percent drug loading efficiency were in the range of 0.698 ± 0.13–1.318 ± 0.22 mm, 175 ± 3.1–280 ± 1.7 s, and 68.34 ± 0.5–94.70 ± 0.7% w/v, respectively. Cumulative percent drug released was 61.8 ± 2.6–94.7 ± 4.1% after 30 min. Polymer concentration at two levels of plasticizer had statistically significant effect on drug loading efficiency and in vitro drug release rate. X2 formulation was found to be excellent in drug loading efficiency and in vitro drug release profiles; hence, drug excipient compatibility studies using Fourier transform infrared spectroscopy and stability studies for 60 days were carried out for X2 formulation and found to be stable. Conclusion: Sodium alginate OSFs containing zolmitriptan was successfully prepared, optimized, and evaluated.
Keywords: Interaction plots; oral soluble film; quality by design; sodium alginate; zolmitriptan